Radiofrequency ablation combined with liposomal quercetin to increase tumour destruction by modulation of heat shock protein production in a small animal model - Yang, Wei (2011)
PURPOSE: To investigate the effect of heat shock protein (HSP) modulation on tumour coagulation by combining radiofrequency (RF) ablation with adjuvant liposomal quercetin and/or doxorubicin in a rat tumour model. METHODS: Sixty R3230 breast adenocarcinoma tumours/animals were used in this IACUC-approved study. Initially, 60 tumours (n = 6, each subgroup) were randomised into five groups: (1) RF alone, (2) intravenous (IV) liposomal quercetin alone (1 mg/kg), (3) IV liposomal quercetin followed 24 h later with RF, (4) RF followed 15 min later by IV liposomal doxorubicin (8 mg/kg), (5) IV liposomal quercetin 24 h before RF followed by IV liposomal doxorubicin 15 min post-ablation. Animals were sacrificed 4 or 24 h post-treatment and gross coagulation diameters were compared. Next, immunohistochemistry staining was performed for Hsp70 and cleaved caspase-3 expression. Comparisons were performed by using Student t-tests or ANOVA. RESULTS: Combination RF-quercetin significantly increased coagulation size compared with either RF or liposomal quercetin alone (13.1 ± 0.7 mm vs. 8.8 ± 1.2 mm or 2.3 ± 1.3 mm, respectively, P < 0.001 for all comparisons). Triple therapy (quercetin-RF-doxorubicin) showed larger coagulation diameter (14.5 ± 1.0mm) at 24 h than quercetin-RF (P = 0.016) or RF-doxorubicin (13.2 ± 1.3 mm, P = 0.042). Combination quercetin-RF decreased Hsp70 expression compared with RF alone at both 4 h (percentage of stained cells/hpf 22.4 ± 13.9% vs. 38.8 ± 16.1%, P < 0.03) and 24 h (45.2 ± 10.5% vs. 81.1 ± 3.6%, P < 0.001). Quercetin-RF increased cleaved caspase-3 expression at both 4 h (percentage of stained cells/hpf 50.7 ± 13.4% vs. 41.9 ± 15.1%, P < 0.03) and 24 h (37.4 ± 7.8% vs. 33.2 ± 6.5%, P = 0.045); with, triple therapy (quercetin-RF-doxorubicin) resulting in the highest levels of apoptosis (45.1 ± 10.7%) at 24 h. Similar trends were observed for rim thickness. CONCLUSIONS: Suppression of HSP production using adjuvant liposomal quercetin can increase apoptosis and improve RF ablation-induced tumour destruction. Further increases in tumour coagulation can be seen including an additional antitumour adjuvant agent such as liposomal doxorubicin.